High-resolution air shower observations with the Square Kilometer Array - Buitink, S.; Bray, J.; Corstanje, A.; Desmet, M.; Falcke, H.; Gayley, K.; Hare, B. M.; Hörandel, J. R.; Huege, T.; James, C. W.; Jhansi, V. B.; Karastathis, N.; et al. (Proceedings of Science, 2024)
The low-frequency part of the Square Kilometer Array will have an extremely high antenna density of roughly 60.000 antennas within one square kilometer, offering exciting new possibilities for high-resolution studies of air showers. Observing with a frequency band of 50-350 MHz, the SKA will cover the energy range between the knee and the ankle, employing beam forming techniques to reach the lower energies. Using standard techniques, the SKA will reach a resolution on Xmax of 10 g/cm2. In addition, the high antenna density allows for the development of new techniques to reconstruct the longitudinal shower development, that can be used to test hadronic interaction models and put additional constraints on the mass composition in the Galactic-extragalactic transition energy range. In this contribution, we review the science case for SKA cosmic-ray detection and the status of the prototype scintillator triggering array.
CRIS-Team Scopus Importer:2025-02-04